Rural Perspectives on Special Education in Transition: Public Law 105-17, Amendments to the Individuals with Disabilities Education Act of 1997 - Terry R. Berkeley (Journal of Research in Rural Education, 1998)
Changes to the policy requiring the provision ofspecial education being provided in the nation's schools have recently been enacted. The 1997Amendments to the Individuals with Disabilities Education Act, Public Law 105-17, extend the values ofequity, efficiency, and choice upon which Public Law 94-142, the Education for All Handicapped Children Act of1975, was enacted and implemented. The changes to the law are subtle, yet significant, and they are geared to the learning and achievement of students with disabilities in the nation's schools. For rural schools, these changes are examinedfrom the view ofefficiency and the rural contexts ofculture, land, and community.